A Single Belief-Changing Psychedelic Experience Is Associated With Increased Attribution of Consciousness to Living and Non-living Entities - Nayak, Sandeep M.; Griffiths, Roland R. (Frontiers in Psychology, 2022)
Introduction: Although the topic of consciousness is both mysterious and controversial, psychedelic drugs are popularly believed to provide unique insights into the nature of consciousness despite a lack of empirical evidence. Methods: This study addresses the question of whether psychedelics change the attribution of consciousness to a range of living and non-living entities. A survey was conducted in 1606 respondents who endorsed a belief changing psychedelic experience. Results: Participants rated their attributions of consciousness to a range of living and non-living entities before and after their psychedelic experience. Superstitious beliefs and belief in freewill were also assessed. From before the experience to after, there were large increases in attribution of consciousness to various entities including non-human primates (63% to 83%), quadrupeds (59% to 79%), (insects (33% to 57%), fungi (21% to 56%), plants (26% to 61%), inanimate natural objects (8% to 26%), and inanimate manmade objects (3% to 15%). Higher ratings of mystical experience were associated with greater increases in the attribution of consciousness. Moreover, the increased attributions of consciousness did not decrease in those who completed the survey years after the psychedelic experience. In contrast to attributions of consciousness, beliefs in freewill and superstitions did not change. Notably, all findings were similar when restricted to individuals reporting on their first psychedelic experience. Discussion: This study demonstrates that, among people who reported belief-changing psychedelic experiences, attribution of consciousness to various entities increases. Future prospective psychedelic drug administration studies that control for expectancies are needed.